Patterns of Local Autonomy in Europe - Ladner, Andreas. author. aut Link
XVIII, 359 p. 59 illus.
Keywords: This book considers local autonomy, measured as a multidimensional concept, from a cross-country comparative perspective, and examines how variations can be explained and what their consequences are. It fills a gap in the literature by providing a comprehensive study of the different components of local autonomy across a large number of countries, over time. It offers a theoretically saturated concept to measure local autonomy and applies it to 39 countries, including all 28 EU member states together with Albania, Georgia, Iceland, Liechtenstein, Macedonia, Moldova, Norway, Serbia, Switzerland Turkey and Ukraine, over a period of 25 years (1990-2014). Andreas Ladner is Professor of Political Institutions and Public Administration at the Swiss Graduate Institute of Public Administration, University of Lausanne, Switzerland. Harald Baldersheim is Professor Emeritus in the Department of Political Science, University of Oslo, Norway. Nikos Hlepas is Associate Professor for Local Self-Government and Regional Administration at the National and Kapodistrian University of Athens, Greece. Nicolas Keuffer is Research Assistant at the Swiss Graduate Institute of Public Administration, University of Lausanne, Switzerland. Carmen Navarro is Associate Professor at the Department of Political Science, University Autónoma of Madrid, Spain. Kristof Steyvers is Professor of Political science, Ghent University, Belgium. Paweł Swianiewicz is Professor in the Department of Development and Local Policy, University of Warsaw, Poland.